The impact of public investment on economic growth in Vietnam - Le, Thi Minh Ngoc; Nguyen, Thi Thuy Huong; Nguyen, Minh Nhat; Truong, Quoc Cuong; Nguyen, Dieu Linh (Edelweiss Applied Science and Technology, 2025)
This paper examines the role of public investment in promoting economic growth in Vietnam, providing a theoretical and empirical framework for understanding its impact. It seeks to evaluate the effectiveness of public investment in stimulating long-term economic development and to propose policy recommendations for improving its efficiency. Accordingly, the research utilizes time-series data from 1995 to 2019 and applies the autoregressive distributed lag (ARDL) model to assess both the short-term and long-term effects of public investment on economic growth. The study also conducts an extensive review of domestic and international literature to establish the theoretical basis for analysis. The findings indicate a significant positive relationship between public investment and Vietnam’s economic growth. However, while public investment contributes to long-term economic expansion, its short-term effects appear less pronounced compared to private and foreign direct investments. Inefficiencies in resource allocation and governance issues are identified as key challenges limiting the effectiveness of public investment. Public investment plays a vital role in sustaining Vietnam’s economic growth, but its efficiency must be enhanced through improved governance, strategic project selection, and effective allocation of resources. Strengthening institutional frameworks and promoting public-private partnerships are crucial to maximizing the benefits of public investment. In addition, the study provides valuable insights for policymakers, emphasizing the need for policy reforms to enhance the efficiency and impact of public investment. Recommendations include legal improvements, decentralization of budget allocation, better financial planning, and increased transparency in investment projects to support sustainable economic development.